1993
DOI: 10.1523/jneurosci.13-12-05301.1993
|View full text |Cite
|
Sign up to set email alerts
|

Apical dendrites of the neocortex: correlation between sodium- and calcium-dependent spiking and pyramidal cell morphology

Abstract: Apical dendrites and somata of layer V pyramidal neurons were recorded with tight-seal patch electrodes in a slice preparation of rat somatosensory cortex. Recording sites were confirmed by measurements of the electrode location and by staining with biocytin. Dendritic recordings were made along the main trunk of the apical dendrite, usually within layer IV, at distances from 100 to 500 microns from the soma. Most cells recorded through the dendrite had a distinct enlargement of the apical trunk around the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
150
1
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(166 citation statements)
references
References 50 publications
(56 reference statements)
14
150
1
1
Order By: Relevance
“…14C). This is in agreement with previous intracellular studies of neocortical pyramidal cells in vivo and in vitro 5,9,30,52 where it was observed that synaptic stimuli can elicit dendritic spikes (reviewed in Ref. 66).…”
Section: Synaptically-evoked Spikessupporting
confidence: 93%
See 2 more Smart Citations
“…14C). This is in agreement with previous intracellular studies of neocortical pyramidal cells in vivo and in vitro 5,9,30,52 where it was observed that synaptic stimuli can elicit dendritic spikes (reviewed in Ref. 66).…”
Section: Synaptically-evoked Spikessupporting
confidence: 93%
“…In inferior olivary cells, this shoulder is mediated by high-threshold dendritic Ca 2+ currents. 35,36 Since pyramidal cells possess similar dendritic conductances, 30,67 and pyramidal neurons generate dendritic Ca 2+ plateaus in the presence of K + channel blockers, 53,67 a similar mechanism probably contributed to the spike shoulder observed here. In computer simulations of Cs + recordings, it was determined that Na + currents generated by the proximal 300 µm of the dendrites contributed to the falling phase of the somatic APs.…”
Section: Influence Of Inhibitory Postsynaptic Potentials On Somatofugmentioning
confidence: 68%
See 1 more Smart Citation
“…Spatial factors may affect the gain increase and its modulation by G sAHP . Na ϩ and Ca 2ϩ spikes generated in apical dendrites (Kim and Connors, 1993;Reuveni et al, 1993;Yuste et al, 1994;Schiller et al, 1997;Stuart et al, 1997;Schwindt and Crill, 1999;Larkum et al, 1999) might cause noise to increase gain in some pyramidal neurons. Noisy current injected into the distal apical dendrite of layer 5 pyramidal cells increases gain for 4 stimulus fluctuation to fire, and its gain increases with noise amplitude.…”
Section: Mechanisms Of Noise Effectsmentioning
confidence: 99%
“…on physiological data from excitatory synapses, where g was set to 1 ms and d to 20 ms (Kim and Connors 1993;Mason et al 1991;Sato and Schall 2001;Sayer et al 1990). Baselines for each SDF were calculated as the mean firing rate during the 1,500 ms immediately preceding stimulus onset.…”
Section: Data Acquisition and Analysismentioning
confidence: 99%